The periodization of Slovene and Czech literatures and the two currents in Czech interwar literature - Pospíšil, Ivo (Primerjalna književnost, 2009)
The author discusses the problem of periodization of Slovene and Czech literatures in general and with regard to the 20th-century interwar period in particular. The Czech and Slovene literatures of the interwar developed similar movements and tendencies, but the divergent political and cultural climate and ideological positions (Marxism, Catholicism) gave various results: Czechs had nearly no Catholic dissidents, rather individualities and extremists, the same as on the avant-garde or communist side. The liberal democratic and religious and spiritual currents in Czech literature are demonstrated on the comparison of Karel Čapek and Jaroslav Durych.
Keywords: Čapek, Karel, 1890-1938; Durych, Jaroslav, 1886-1962; primerjalna literarna veda; Slovene literature; slovenska književnost; češka književnost; Czech literature; literatura in ideologija; literarna periodizacija; modernizem